Study of thermal chiller under tropical climate conditions - Loh, Marcus Hong Wah (2019)
Researchers and scientist have widely studied adsorbent materials for various use. Usage includes storage of gases, purification media in wastewater treatment, and cooling applications. This report focuses on metal-organic-framework-801 (MOF-801) with added Methyl functional group, ( -CH3) for adsorption chiller applications. The experimental results first present the characterization of (CH3)2 – MOF – 801, followed by simulation results of a two bed adsorption chiller through inputting the experimentally confirmed adsorption isotherms and kinetics data. The experimental results showed improved adsorption kinetics over the parent MOF-801, and this marked an improve in performance in adsorption chiller application. The numerical simulation based on the experimentally confirmed adsorption isotherms and kinetics yielded a 31.1% increase in COP and 48% percent increase in COP at a low hot water temperature of 60°C. The numerical modelling of a 2-bed adsorption chiller yielded a chill water output of 12°c with hot water temperature of 60°C , cooling water of 30°C, with cycle time of 850s and switch time of 30s. From the simulation study, it is concluded that (CH3)2 – MOF – 801 shows promising results in terms of specific cooling capacity (0.45 kW/kg) and coefficient of performance (≈0.5) which are higher than those of silica-gel-water / zeolite-water systems. The learning outcome of this project includes the synthetization of MOF, understanding of adsorption isotherms and kinetics, working principles of adsorption-desorption chiller, as well as the dynamic behaviour of an adsorption-desorption chiller due to influencing parameters.